2017
DOI: 10.1093/humrep/dex215
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diseases and aneuploidies can be detected with a single blastocyst biopsy: a successful clinical approach

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…In PGD programs it is not uncommon for embryos to fail genetic testing, and in our own clinic we have previously reported a failure rate of 5.0% from more than 5,000 PGS blastocysts with the use of CGH or NGS (17). This is similar to others, including Capalbo et al who reported a failure rate of 2.7% from almost 1,000 PGS blastocysts with the use of CGH (24) and Minasi et al who reported a failure rate of 4.9% from 1,122 blastocysts screened for inherited genetic disorders in combination with PGS using CGH (25). We therefore also examined the impact of performing a second blastocyst biopsy because of failed genetic testing.…”
Section: Discussionsupporting
confidence: 80%
“…In PGD programs it is not uncommon for embryos to fail genetic testing, and in our own clinic we have previously reported a failure rate of 5.0% from more than 5,000 PGS blastocysts with the use of CGH or NGS (17). This is similar to others, including Capalbo et al who reported a failure rate of 2.7% from almost 1,000 PGS blastocysts with the use of CGH (24) and Minasi et al who reported a failure rate of 4.9% from 1,122 blastocysts screened for inherited genetic disorders in combination with PGS using CGH (25). We therefore also examined the impact of performing a second blastocyst biopsy because of failed genetic testing.…”
Section: Discussionsupporting
confidence: 80%
“…Title and abstract screening resulted in 73 papers. Full text screening resulted in 26 publications fulfilling the inclusion criteria . No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, embryo transfer was performed in 81% of cycles (1688/2084) in the control group not receiving aneuploidy screening while only 67% of cycles had transferable embryos following screening for aneuploidy (212/317) . In another study, of 304 cycles, 71% of cycles had suitable embryos for transfer following PGT‐M/SR, which was reduced to 60% following aneuploidy screening . Minasi et al reported the percentage of cycles with no transferable embryos following aneuploidy screening to be similar in patients affected by monogenic disorders and structural rearrangements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations